THE RELATIONSHIP OF KNOWLEDGE AND CONFIDENCE WITH THE BEHAVIOR OF ADDRESS TO TAKING DIABETES MELLITUS MEDICATION IN TYPE 2 DIABETES MELLITUS PATIENTS AT BHAYANGKARA BRIMOB HOSPITAL - Nuryanti, Euis; Cusmarih, Cusmarih (HEARTY, 2025)
Background: The incidence of DM is increasing, if not treated properly it can cause various complications in the body. DM complications can cause increased morbidity and mortality. The success of Diabetes Mellitus treatment is greatly influenced by the patient's compliance with maintaining their health Research Purpose: To determine the relationship between knowledge and belief and compliance behavior in taking diabetes mellitus medication in type 2 diabetes mellitus patients at Bhayangkara Brimob Hospital. Research Method: The research approach used in this research is cross-sectional. The population in this study was 1410 DM patients in 2023. The sample required is 93 respondents. The sampling technique for respondents used a simple random sampling technique. The instrument in this research was to use a questionnaire. Researchers used the Chi Square test. Research Results: The results of statistical tests on the relationship between knowledge and compliance behavior obtained a P value = 0.005 and the results of statistical tests on the relationship between beliefs and compliance behavior obtained a P value = 0.001. Conclusions and Suggestions: There is a relationship between knowledge and belief and compliance behavior in taking diabetes mellitus medication in type 2 diabetes mellitus patients at Bhayangkara Brimob Hospital. Suggestions for Hospital Management: Create educational classes for patients, especially type 2 DM sufferers, to understand medication compliance